Kasus Morfea Tipe Linier (En Coup de Sabre) pada Wanita Berusia 20 Tahun - Achmad Satya Negara; Arie Kusumawardhani (MEDICINUS, 2023)
Background: Morphea is a chronic inflammatory disease characterized by sclerosis of the skin which belongs to the group of idiopathic sclerotic diseases. Frontoparietal linear morphea is a unilateral atrophy linear plaque on the forehead that can extend to the eyebrows, nose, lips, and scalps, causing alopecia. The aim of this case report is to establish the diagnosis of frontoparietal linear morphea. Case: A 20-year-old woman presented with a dark brown spot on her forehead. Histopathological examination showed a basket-weave hyperkeratosis and flattening of the rete ridges of epidermal layer, and pigmented cells in the basal cells of the dermal-epidermal junction. Based on the results of physical examination and histopathology, patient was diagnosed with linear morphea en coup de sabre. Patient was treated with topical and systemic corticosteroid. Discussion: Morphea is a rare fibrotic disease of the skin and underlying tissue, characterized with diffuse thickening, induration, or atrophy. Histopathological biopsy examination can be used to confirm the diagnosis and rule out differential diagnosis. Histopathological biopsy of early phase morphea can show inflammation, the dermis looks dense with thickened collagen fibers accompanied by inflammatory cells, especially perivascular lymphocytes between collagen fibers, flattening of the epidermal rete ridges, and atrophy. Topical therapy with corticosteroid as anti-inflammatory drug can be used in active lesions of early-stage linear morphea.